ERCC1/XPF Is Important for Repair of DNA Double-Strand Breaks Containing Secondary Structures - Shibo Li; Hongyan Lu; Zi Wang; Qing Hu; Hongjun Wang; Rong Xiang; Takuya Chiba; Xiaohua Wu (iScience, 2019)
Summary: The structure-specific endonuclease ERCC1/XPF plays an important role in nucleotide excision repair and interstrand cross-link repair. In this study, we identified new functions of ERCC1/XPF in DNA double-strand break (DSB) repair. We found that the conserved function of ERCC1/XPF to remove non-homologous sequences at DSBs is a rate-limiting step for homologous recombination in mammalian cells, and more importantly, we uncovered an indispensable role of ERCC1/XPF in repair of DSBs containing DNA secondary structures, including the structure-prone AT-rich DNA sequences derived from common fragile sites and G-quadruplexes (G4s). We also demonstrated a synthetic lethal interaction of XPF with DNA translocase FANCM that is involved in removing DNA secondary structures. Furthermore, inactivation of XPF sensitizes FANCM-deficient cells to G4-interacting compounds. These results suggest an important function of ERCC1/XPF in protecting DNA secondary structures and provide a rationale for targeted treatment of FANCM-deficient tumors through inhibition of XPF. : Biological Sciences; Molecular Biology; Cell Biology Subject Areas: Biological Sciences, Molecular Biology, Cell Biology